Customer Ratings in the Shopee Marketplace Using Consumer Trust as an Intermediate Variable and Their Influence on Purchase Decisions - Febby Herlambang; wachjuni wachjuni; Wely Hadi Gunawan (Universitas Kuningan, 2023)
This research aimed to examine the influence of customer reviews and ratings on purchase decisions through consumer trust. The population in this study was the West Java society who have used or made purchases on the Shopee marketplace, with a sample size of 180 respondents selected using probability sampling technique. The study utilized 18 statement indicators on a scale of 1-10. Sampling and analysis of the results were conducted using the Structural Equation Modeling (SEM) method with AMOS version 23, which was employed to test the direct influence of customer reviews and ratings on purchase decisions through consumer trust as an intervening variable. The research instrument consisted of a physical questionnaire containing statements and was distributed directly to the respondents. The findings from the tested hypotheses concluded that (1) customer reviews have a positive and significant influence on consumer trust, (2) ratings have a positive and significant influence on consumer trust, (3) customer reviews have a positive and significant influence on purchase decisions, (4) ratings do not influence on purchase decisions, (5) consumer trust has a positive and significant influence on purchase decisions, (6) customer trust partially mediated the influence of customer reviews on purchasing decisions, and (7) customer trust fully mediated the influence of ratings on purchasing decisions.